Investigating Compliance with Standard Precautions During Residency Physicians in Gynecology and Obstetrics (Clinics, 2016)
OBJECTIVES: Physician compliance with standard precautions is important in the specialty of gynecology and obstetrics because of the high frequency of invasive procedures. The current study investigated compliance with standard precautions among resident physicians working in gynecology and obstetrics. METHOD: A cross-sectional study was conducted among resident physicians in gynecology and obstetrics in their first (R1), second (R2) and third (R3) years of residency at a teaching hospital in a city in São Paulo. A structured questionnaire that included demographic and professional aspects and the Standard Precautions Adherence Scale were used to collect data. Statistical analysis was performed using IBM® SPSS version 20. Ethical aspects were considered. RESULTS: Fifty-eight resident physicians participated in the study. Of the enrolled participants, 27 (46.6%) were in R1, 12 (20.7%) were in R2 and 19 (32.8%) were in R3. The standard precautions compliance score was 4.1, which was classified as intermediate. There were no significant differences in the compliance scores of the resident physicians across the three years of residency (H=2.34, p=0.310). CONCLUSION: Compliance with standard precautions among resident physicians was intermediate. Preventive measures in clinical practice are not fully adopted in the specialty of gynecology and obstetrics. More important, many professionals claimed lack of sufficient training in standard precautions in the workplace. Such circumstances should draw the attention of hospital management with regard to occupational health risks.